Using Collaborative Course Development to Achieve Online Course Quality Standards - Chao, Ining Tracy; Saj, Tami; Hamilton, Doug (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2010)
The issue of quality is becoming front and centre as online distance education moves into the mainstream of higher education. Many believe collaborative course development is the best way to design quality online courses. This research uses a case study approach to probe into the collaborative course development process and the implementation of quality standards at a Canadian university. Four cases are presented to discuss the effects of the faculty member/instructional designer relationship on course quality, as well as the issues surrounding the use of quality standards as a development tool. Findings from the study indicate that the extent of collaboration depends on the degree of course development and revision required, the nature of the established relationship between the faculty member and designer, and the level of experience of the faculty member. Recommendations for the effective use of quality standards using collaborative development processes are provided.